KONTRIBUSI EKSISTENSIALISME DALAM PERSPEKTIF PENDIDIKAN AGAMA ISLAM - Aswati Aswati; Husnul Khotimah; Habibur Rahman; Ririn Maghfirah; Duwi Lismawati (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UNSIQ Jawa Tengah, 2023)
Education and philosophy have an unavoidable relationship. This is because the philosophy of education is the basis of a foundation in an education system. Philosophy of education becomes a guide in efforts to improve, increase progress and a strong basis for the upholding of the education system. Not a few educational figures and thinkers doubt the position of schools as educational institutions whose function is to prepare future generations. The character's scathing criticism stated that educational institutions (policies, teachers) have positioned themselves as means of controlling creation and curbing individual freedom, even though each individual has his own privileges and thoughts in taking action. This research takes a qualitative approach to its investigation. Collecting data using library research methods by examining various literature. Existentialism has one side which is in line with Islamic education which aims to form a complete human being, his mind and heart, spiritual and physical; morals and skills. However, in terms of objectives, Islamic education also emphasizes physical and spiritual balance towards perfection and completeness of the true meaning of humanity.